PEMELIHARAAN MESIN DISC MILL SENTRA PETERNAKAN RAKYAT (SPR) CINAGARBOGO - Adhan Efendi; Roni Suhartono (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2019)
Sentra Rakyat Rakyat (SPR) is a collection of cattle breeders in the Subang Regency area. SPR aims to raise beef cattle and provide ruminant feed. Ruminant feed made from corn hump waste. The disc mill machine is used in the process of destroying corn lumps into flour, flour from the results of this corn hump will be combined with other components to form a ruminant feed for cattle feed. The process of making feed is disrupted because the disc mill machine is damaged. This study aims to detect damage to the engine and clasification maintenance of disc mill machines using the Inspection, Medium Repair, Small Repair, and Overhaul (ISMO) methods. The method used in data collection is in the form of interviews and observations. Data is analyzed qualitatively description. The results of this study are (1) machine damage, namely the disc mill cutting blade allowance caused by the destruction of the engine shaft bearing; (2) More maintenance is needed on filter sections, cutting blades, crankshafts, v-belts and bearings.